Improving Production Efficiency and Packaging Innovation among Women-Owned MSMEs of FKKS in Ciracas District through Participatory Production Training - Pristina Hermastuti; Enung Siti Saodah; Dodi Prastuti; Diah Pranitasari; Iman Sofyan Suriawinata (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Women-owned micro, small, and medium enterprises (MSMEs) often face technical production constraints that hinder business growth, including inefficient workflows, inconsistent raw material quality, limited innovation, and weak packaging competitiveness, common among informally managed home-based enterprises. This community service activity aimed to strengthen the production capability of women MSMEs under the Forum Komunikasi Komite Sekolah (FKKS) in Ciracas District through participatory production training, focusing on workflow efficiency, raw material standardization, product diversification, and packaging improvement. Thirty women entrepreneurs participated through workshops, demonstrations, hands-on practice, and four weeks of mentoring. Results show substantial behavioral change: 81% established raw material standards, 93% developed new product variants or improved packaging, 90% applied more efficient workflows, and 82% achieved better product consistency. These findings indicate that practical, production-oriented assistance can meaningfully improve technical capability and competitiveness among women-led MSMEs.